Buried : the 1982 Alpine Meadows avalanche [videorecording (DVD)] - Plehn, Jim; Heywood, Larry; Watson, Meredith (Kino Lorber, 2022)
In 1982, a massive avalanche descended on Alpine Meadows Ski Resort in Lake Tahoe, California that triggered a desperate five day search for eight missing people. Buried chronicles the third deadliest avalanche in US history, the miraculous rescue efforts and the traumas that still haunt the survivors today.